SYSTEMATIC LITERATURE REVIEW : PENGEMBANGAN KEMAMPUAN PEMECAHAN MASALAH MELALUI PEMBELAJARAN INOVATIF - Rohyati Rohyati; Fitrianto Eko Subekti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this study is to determine whether problem-based learning models have an influence on increasing students' ability to solve mathematical problems. The Systematic Literature Review (SLR) method was the method used in this study. The systematic stage of this review literature is planning, reviewing and documentation. The data analysis technicque used is data grouping, dara analysis, and data conclucion. The results of the study showed: (1) There is an increase in students' ability to solve problems using the Problem-Based Learning model, (2) the Problem-Based Learning model becomes an alternative for teachers in developing students' problem-solving skills, (3) comic media becomes an alternative in delivering material as a driver of problem-solving abilities. students, (4) students' ability to solve problems is influenced by various factors, it is necessary to optimize the factors that influence student problem solving.